Penyuluhan Tentang Imunisasi TT Pada Ibu Hamil DI Desa Joring Natobang Kecamatan Padangsidimpuan Angkola Julu Tahun 2020: Immunisasi, Tetanus Toksoid, Ibu Hamil - Batubara, Novita Sari; Siregar, Rya Anastasya (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
Immunity to tetanus can only be obtained through tetanus toxoid immunization. Pregnant women who get tetanus toxoid immunization in their body will form tetanus antibodies. The purpose of this PKM is to motivate pregnant women about the importance of doing TT (Tetanus Toxoid) Immunization. This PKM activity was carried out by means of health education methods using leaflet media to 15 pregnant women in the village of Joring Natobang. The results of this counseling activity were continued by providing an evaluation of pregnant women, namely questions and answers about the TT (Tetanus Toxoid) material. Pregnant women can be responsible and explain well the questions asked by the counselor. PKM activities that were carried out went well. Pregnant women in Joring Natobang village who participated seemed enthusiastic in participating in the activity.